Exploring Variation in Root Canal Morphology of Maxillary Second Premolars: A Cone-Beam Computed Tomography Study in a Pakistani Subpopulation: Root Canal Morphology of Maxillary Second Premolars - Bano, Shaher; Asif, Shahzadi Minahil; Shehzad, Fatima; Idrees, Nida; Ihsan, Ali; Anwar, Malik Adeel (Pakistan Journal of Health Sciences, 2024)
A comprehensive knowledge of anatomy of roots and root canals was a key for successful treatment outcomes. Maxillary second premolars often display variability in root and canal numbers. Traditional 2-dimensional imaging techniques have limitations in exact diagnosis of dental anatomy, encouraging the practice of Cone Beam Computed Tomography (CBCT) for comprehensive three-dimensional imaging. Objective: To explore the variations in the number of roots and root canals in maxillary second premolars using CBCT. Methods: The current study was a retrospective and conducted at the Radiology department of Fatima Memorial Hospital College of Dentistry, Lahore. A total of 143 CBCT scans with completely formed roots were included. Data were analyzed using Planmeca Romexis imaging software and statistical analysis was performed using SPSS version 23.0. Results: Among 143 individuals, the majority exhibited one root and one canal in maxillary second premolars. In terms of root number, 77% of the 2nd premolars had a single root and 23% had two roots. In relevance of root canals, 62.5% were found to have a single canal and 37.5% had two root canals. However, no any case was found having three roots and canals. Bilateral symmetry in root canal patterns was observed in most cases, with statistically significant differences between genders. Conclusions: The findings of this study may contribute to the understanding of variations in dental anatomy in Pakistani population and emphasize the importance of one’s treatment approaches for optimal patient care.